Aprenentatge creatiu per projectes per impulsar la innovació tecnològica - José D Badia (Servei de Formació Permanent i Innovació Educativa, Universitat de València, 2017)
This paper shows the results of the application of a project-based learning methodology that blended flipped classroom and face-to-face sessions, along with creativity and lateral thinking techniques, to integrate the expected concepts and procedures of technology innovation and boost entrepreneurship among students of Master's degree in chemical engineering. The constructive alignment between the expected learning outcomes and skills with the proposed activities and assessment methods was decisive in the design of the methodology, which tractor activity was the creation of an innovation project. The use of techniques of creativity promoted lateral thinking and originality in the definition of projects. Active methodologies provoked team engagement and collaborative learning, enhanced participation and stimulated intrinsic motivation. The grades obtained by all groups in their projects, given by external evaluators, were relevant, thus pointing out the quality and impact of their proposals. There was a general satisfaction on students, with special emphasis of the transcendence at a professional level, thus showing the potential of this methodology to boost entrepreneurship in technology innovation.